2014
DOI: 10.1149/06107.0101ecst
|View full text |Cite
|
Sign up to set email alerts
|

3C-SiC on Si: A Biocompatible Material for Advanced Bioelectronic Devices

Abstract: Silicon carbide (SiC) has long been known as a robust semiconductor with superior properties to silicon for electronic applications. The cubic form of SiC, known as 3C-SiC, has been researched for non-electronic applications, such as MEMS and biosensors. In particular, our group has demonstrated that 3C-SiC is one of the few semiconductor materials that possesses both bio- and hemacompatibility, thus opening up a plethora of applications for this material. We have pioneered several biomedical devices using 3C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…In vitro and in vivo studies of 3C-SiC, based on ISO 10993, have shown that this material is suitable for use in biomedical devices [9]. This is consistent with previous literature reports of SiC bio-and hemacompatiblity and the successful clinical use of a-SiC as a non-thrombogenic coating for arterial heart stents.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In vitro and in vivo studies of 3C-SiC, based on ISO 10993, have shown that this material is suitable for use in biomedical devices [9]. This is consistent with previous literature reports of SiC bio-and hemacompatiblity and the successful clinical use of a-SiC as a non-thrombogenic coating for arterial heart stents.…”
Section: Discussionsupporting
confidence: 87%
“…We propose the use of 3C-SiC as the base material for numerous long-term biomedical devices [8]. We also have proposed that a-SiC can be utilized as a biocompatible insulator to facilitate reduced electronic cross talk between adjacent conductors in multi-site neural recording probes and MEAs [9]. We have demonstrated the fabrication of several planar neural probes as well as the very limited glial reaction to these probes at 1 month after implantation [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports on the biomedical application of several forms of SiC by proving biocompatibility of SiC [203,[242][243]. Li et al [242] have shown the superior mechanical and tribological properties of SiC that make it an ideal material for use in orthopedic and other biomedical applications.…”
Section: Bio-medical Applicationsmentioning
confidence: 99%
“…This property can be very helpful for devices subjected to high temperature and compares favorably to challenging wide bandgap materials such as gallium nitride. Furthermore, SiC is also known as a biocompatible material [2], which is deeply valued for biologic applications [3], and is resistant to high-radiative environments [4]. Within this frame, the cubic polytype of SiC (3C-SiC) is the only one that can be grown on a host substrate with the huge opportunity to grow only the silicon carbide thickness required for the targeted application.…”
Section: Introductionmentioning
confidence: 99%